2020
DOI: 10.3390/polym12020474
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Peptide Affinity and Stability by Complexing to Cyclodextrin-Grafted Ammonium Chitosan

Abstract: Cyclodextrin-grafted polymers are attractive biomaterials that could bring together the host–guest complexing capability of pristine cyclodextrin and the pharmaceutical features of the polymeric backbone. The present paper is aimed at characterizing the potential application of ammonium–chitosan grafted with 2-methyl-β-cyclodextrin (N+-rCh-MCD) as the functional macromolecular complexing agent for the oral administration of the neuropeptide dalargin (DAL). Specific NMR characterization procedures, along with U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…The free DAL sample was readily degraded in the apical chamber by the enzyme activity of the monolayer cells, and thus only 8.67 ± 0.80% of the drug was still present at the end of the experiment (3 h) [15]. The peptide degradation was such that its presence in the basolateral chamber could never be evidenced, in agreement with previous studies [15].…”
Section: Permeation Across Caco-2 Monolayerssupporting
confidence: 89%
See 2 more Smart Citations
“…The free DAL sample was readily degraded in the apical chamber by the enzyme activity of the monolayer cells, and thus only 8.67 ± 0.80% of the drug was still present at the end of the experiment (3 h) [15]. The peptide degradation was such that its presence in the basolateral chamber could never be evidenced, in agreement with previous studies [15].…”
Section: Permeation Across Caco-2 Monolayerssupporting
confidence: 89%
“…In the present work in particular, an N + -rCh-CD was obtained, which contained 52% by weight of MCD and was much more soluble than the polymer conjugates obtained previously [13,14], therefore allowing a better handling. NMR studies with model solutions containing DAL and MCD [15] in physiological conditions showed that the DAL-cyclodextrin interaction consisted in DAL inclusion within the oligosaccharide cavity and mainly involved the aromatic moieties of the tyrosine units, although interactions with phenylalanine and the alkyl residues of the leucine and alanine units were also observed. A stronger interaction of the aromatic than the aliphatic components resulted from the NMR studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data showed a greater ability of QA-Ch-MCD to protect DAL from degradation by α-chymotrypsin compared to the physical mixture of the precursors. This ability can be attributed to a synergistic cooperation of cyclodextrin and polymer, which occurs only when the former is covalently linked to the latter [57].…”
Section: No-[nn-diethylaminomethyl(diethyldimethylene Ammonium)nmetmentioning
confidence: 99%
“…The association constant of DAL with the polymeric derivative is one order of magnitude higher than that with the pristine cyclodextrin (K a : 2600 M −1 and 120 M −1 , respectively). Additionally, N + -rCh-MCD shields DAL from enzymatic degradation in gastrointestinal in vitro models with a three-fold time delay, suggesting a future pharmaceutical exploitation of the polymeric derivative [13].…”
mentioning
confidence: 99%